Polemic of the Application of Electronic Certificates in Indonesia - Lintang Kalbuhardi; Khunsul Yaqin (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2021)
The purpose of this study is first, to analyze the efficiency of electronic certificates applied in remote areas of Indonesia. Second, to analyze the Land Deed Making Officials are able to compensate in making the Deeds. This research uses normative legal research methods. This research concludes: the issuance of the Regulation of the Minister of Agrarian Spatial Planning of the National Land Agency Number 1 of 2021 concerning Electronic Certificates has a good purpose to assist the community in ownership of their land rights, the existence of electronic certificates is also expected to give a modern and advanced impression for the development of important documents in Indonesia, can be accessed easily by the public and related agencies in carrying out other legal actions. The tendency of disputes due to irresponsible parties can also be minimized such as double certificates, but apart from that all polemics related to electronic certificates also appear among the public and Land Deed Authorities, this polemic gives a doubt due to the security of people's personal data stored by The Ministry of ATR / BPN is feared to leak so that the personal data is misused by irresponsible parties. PPATs who take care of community legal actions in making Land Deeds are also required to improve the performance of their offices to keep up with the changes and developments given by the Ministry of ATR / BPN, so that PPAT has to adjust itself even though in each area the obstacles to internet infrastructure are not all the same speed, as well as electricity infrastructure. which sometimes goes out.